Validación de una herramienta clínica para la evaluación de obstrucción bronquial y manejo en lactantes con síndrome broncoobstructivo, en hospitalización de pediatría del hospital Isidro Ayora, Loja. - Paz Soto, María Auxiliadora. (2014)
The broncoobstructivo baby syndrome (SBOL) is the main reason for consultation with respiratory disease in children under 2 years. In some countries in South America since 2008, a brief hospitalization scheme was implemented through the valuation of paintings by SBO scale Tal, as amended. With the goal of a proper assessment, treatment and hospitalization in patients with SBO has conducted this study. In the present investigation were enrolled prospectively infants between 1 and 24 months with diagnosis SBOL without risk factors who entered hospitalization, six months being evaluated with the scale of Tal, modified influencing initial management , evolution and reduction of hospital days. 40 patients in whom Tal score at admission, mostly mild cases 50% were evaluated included; required treatment with oxygen 30%, 77.5 % antibiotics , bronchodilators by 100 % , and steroids in 65%. The scale score at discharge, is 100 % for mild stage, and finally the hospital stay was 1-3 days due to the proper use of the scale of Tal. Brief hospitalization strategy, by applying the scale of Tal, and tracking its evolution and implementation of timely and appropriate treatment, proved useful for handling SBOL.